Immune‐Related Encephalitis in a Patient With Pleural Mesothelioma: Case Report - Fumie Onishi; Naofumi Hara; Moeko Ota; Kiriko Onishi; Yusuke Fujioka; Hisaaki Tanaka; Nobukazu Fujimoto (Respirology Case Reports, 2026)
ABSTRACT A 69‐year‐old man who was a former plumber with a history of occupational asbestos exposure was diagnosed with unresectable pleural mesothelioma. Six months after initiation of combination therapy with ipilimumab and nivolumab, he presented with an altered level of consciousness and extrapyramidal symptoms and was diagnosed with immune‐related encephalitis. Although high‐dose corticosteroid therapy and intravenous immunoglobulin led to partial improvement in his level of consciousness, the response was limited. Immune‐related encephalitis is rare, especially in association with pleural mesothelioma. Optimal management of the condition needs to be established.